Impairment of adult male reproductive function in rats exposed to ethanol since puberty - Oliva, Samara U.; Messias, Alessandra G.; Silva, Daniela A. F.; Pereira, Oduvaldo C. M.; Gerardin, Daniela C. C.; Kempinas, Wilma G. (Elsevier B.V., 2006)
The objective of this work was to evaluate reproductive function in adult male rats exposed to ethanol since puberty. Male Wistar rats, 50 days old, received a liquid diet with 36% of the daily calories derived from ethanol or an isocaloric control diet for 55 days. The ethanol treatment impaired sexual behavior and only 22% of these rats reached ejaculation. The fertility of ethanol-treated animals was significantly reduced, mainly after natural mating. Serum testosterone levels, daily sperm production and sperm count in the epididymis were also significantly diminished after ethanol treatment, associated with an acceleration of the sperm transit time in the cauda epididymidis, decrease in sperm motility and increased percentage of abnormal shaped sperm cells. The results showed that chronic consumption of ethanol beginning at puberty impairs the reproductive function of adult male rats. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ethanol; male reproductive toxicology; Wistar rat; epididymis; sperm; fertility; puberty; in utero artificial insemination